2018
DOI: 10.3758/s13414-018-1546-3
|View full text |Cite
|
Sign up to set email alerts
|

How social is social inhibition of return?

Abstract: A number of studies have shown that the motor actions of one individual can affect the attention of an observer. In one notable example, "social inhibition of return," observers are relatively slow to initiate a response to a location where another individual has just responded. In the present article we examine the degree to which this phenomenon can be considered a social effect. We find that unlike the related social, or "joint," Simon effect, social inhibition of return is not influenced by competitive ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
3
5
0
Order By: Relevance
“…This difference between same-responses and different-responses reflects the well-established social IOR, i.e., the phenomenon of slowed return-responses to locations previously acted upon by another individual (Welsh et al, 2005). This result indicates -in line with previous research -that the social IOR occurs not only in live twoperson settings where participants perform manual reaching responses, but also if participants interact with a co-actor who is not physically present (see Atkinson et al, 2018;Doneva & Cole, 2014;Nafcha et al, 2020b; but see also Skarratt et al, 2010) and if responses are keypresses (see Manzone et al, 2017;Nafcha et al, 2020b).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This difference between same-responses and different-responses reflects the well-established social IOR, i.e., the phenomenon of slowed return-responses to locations previously acted upon by another individual (Welsh et al, 2005). This result indicates -in line with previous research -that the social IOR occurs not only in live twoperson settings where participants perform manual reaching responses, but also if participants interact with a co-actor who is not physically present (see Atkinson et al, 2018;Doneva & Cole, 2014;Nafcha et al, 2020b; but see also Skarratt et al, 2010) and if responses are keypresses (see Manzone et al, 2017;Nafcha et al, 2020b).…”
Section: Discussionsupporting
confidence: 81%
“…Even though the present study did not primarily aim at contributing to the debate on how social the social IOR actually is (see, e.g., Atkinson et al, 2018;Doneva & Cole, 2014;Doneva et al, 2017;Nafcha et al, 2020a, b;Skarratt et al, 2010), it still makes a relevant contribution in the following respects. First, it reaffirmed previous findings showing that the social IOR occurs not only in live two-person settings but also if participants interact with a co-actor who is not physically present (compare Atkinson et al, 2018;Doneva & Cole, 2014;Nafcha et al, 2020b).…”
Section: The Sociality Of the Social Iormentioning
confidence: 96%
See 1 more Smart Citation
“…It is the case that an experimental design which can effectively distinguish between the mere effects of motion alone and movement of a limb remain elusive due to the overlapping nature of the characteristics of the two categories of stimuli and potential influence of top-down influences of belief in the animacy of the stimulus (see Chandler-Mather, Welsh, Sparks, & Kritikos, in press). Nonetheless, given the substantial behavioural and neurophysiological evidence that cortical regions that are activated during the execution of action are also activated during the observation of movement (e.g., Mulligan et al, 2016aMulligan et al, , 2016bRizzolatti & Craighero, 2004) and that some social effects met the minimum criteria to be considered social (e.g., Atkinson, Millett, Donveva, Simpson, & Cole, 2018), it remains our contention that it is the sensorimotor activation during the execution and observation of goal-direct human movement Future research will need to be conducted to definitively distinguish these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…We found that highcooperative contexts increased inhibition of return effects. Other research, however, was unable to document any change in social inhibition of return effects when participants carried out a joint reaching task either as a cooperation or a competition (Atkinson et al, 2018), interacted with a similar or dissimilar interaction partner (Dalmaso et al, 2021), or competed versus cooperated in a joint perspectivetaking task (Surtees et al, 2021). One possibility is that if the interaction partner is rendered highly salient in two experiments conditions, participants co-represented their partner's task in both experimental conditions, resulting in a null finding.…”
Section: Theoretical Implicationsmentioning
confidence: 98%